Clinical Features and Risk Factors Analysis for Hemorrhage in Adults on ECMO - Hu, Wenwen; Zhang, Jing; Wang, Meifang; Chen, Wei; Chai, Lin; Leung, Elaine Lai-Han; Tang, Yijun (Frontiers in Medicine, 2021)
Background: The use of extracorporeal membrane oxygenation (ECMO) to support critically ill patients with cardiorespiratory dysfunction has increased over the last decades. However, hemorrhagic complications occur frequently during ECMO support, and this has a significant impact on morbidity and mortality. Thus, this study aimed to identify the risk factors for hemorrhage in patients receiving ECMO. Methods: Our retrospective study included 60 patients, who were admitted to the Taihe Hospital in Shiyan City, Hubei Province, China from February 2017 to October 2020. About 18 patients developed hemorrhagic complications, and 42 patients did not demonstrate such complications. Data regarding patient demography, laboratory tests, and clinical manifestations prior to ECMO were collected to analyze their clinical features. Univariable and multivariable logistic analyses were used to explore the risk factors for hemorrhage in adults on ECMO. The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of the binary logistic model. The amount of blood transfusions was compared between the two groups, and the activated partial thromboplastin time (APTT), platelet count, and hemoglobin level before the initiation of ECMO. Results: Logistic analysis showed that a longer duration of ECMO support, higher APTT, and lower platelet count prior to ECMO were independent risk factors for hemorrhage in adults on ECMO. In addition, we found that the cannula site was the most common bleeding site. Most bleeding events occurred within the first 3 days of ECMO therapy. After the ECMO initiation, APTT was prolonged while the platelet count and hemoglobin levels were decreased. The amount of blood transfusion was significantly higher in the hemorrhage group than in the non-hemorrhage group. Conclusions: Clinicians should evaluate the risk of hemorrhage based on the coagulation function of patients, underlying disease, and the duration of ECMO support. In the first 3 days during ECMO support, special attention should be given to the cannula site, mucosal, and dermal regions, and digestive tract to detect any signs of hemorrhage. Moreover, increasing the platelet count transfusion threshold and accurately determining the amount of blood transfusion required may prevent bleeding events.